2012
DOI: 10.1111/j.1600-0706.2012.20825.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of macroalgal assemblages from rockpools to climate change: effects of persistent increase in temperature and CO2

Abstract: Anthropogenically induced global climate change has important implications for marine ecosystems with unprecedented ecological and economic consequences. Climate change will include the simultaneous increase of temperature and CO2 concentration in oceans. However, experimental manipulations of these factors at the community scale are rare. In this study, we used an experimental approach in mesocosms to analyse the combined effects of elevated CO2 and temperature on macroalgal assemblages from intertidal rock p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 63 publications
(94 reference statements)
3
41
0
2
Order By: Relevance
“…For example, rising temperature due to global warming is a large concern and has received considerable attention in recent decades (Sinutok et al 2011, Olabarria et al 2013. Sinutok et al (2011) found that elevated temperature amplified the negative effects of CO 2 on 2 Halimeda spp.…”
Section: Synergistic Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, rising temperature due to global warming is a large concern and has received considerable attention in recent decades (Sinutok et al 2011, Olabarria et al 2013. Sinutok et al (2011) found that elevated temperature amplified the negative effects of CO 2 on 2 Halimeda spp.…”
Section: Synergistic Effectsmentioning
confidence: 99%
“…Among other temperate coralline algae, reported responses include decreased calcification, growth, MgCO 3 content, total inorganic content and reproduction rates under elevated CO 2 (Martin & Gattuso 2009, Russell et al 2009, Cumani et al 2010, Hofmann et al 2012a, Olabarria et al 2013. In environments impacted by natural seafloor CO 2 vents, benthic and epiphytic crustose coralline algae (CCA) are much lower in abundance compared to unimpacted areas (Hall-Spencer et al 2008, Porzio et al 2011).…”
Section: Temperate Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two main approaches have been followed: (1) experimental approaches designed as factorial experiments, incubating macroalgae for days or months at different growth temperatures according to the future predicted scenarios, and evaluating the interactive responses with other variables, such as acidification, UV radiation (UVR), and nutrient availability, amongst others (Baulch et al 2003, Hoppe et al 2008, Porzio et al 2011and (2) field studies of seaweeds growing at their temperature limit for growth and reproduction, while monitoring the temporal and spatial variation of temperature and other variables (Viejo et al 2011, Martínez et al 2012. Most investigations have been conducted on individual species separately, rather than communities (Olabarria et al 2013), although it has been reported that community-level impacts might be less noticeable (Kroeker et al 2010). Moreover, studies on the effect of global climate changes on aquatic organisms have mostly been conducted with 1 or 2 variables, and interactions between multiple factors have scarcely been studied (Franklin & Foster 1997, Gordillo et al 2001, Bischof et al 2006a, Häder et al 2007).…”
Section: )mentioning
confidence: 99%
“…Climate change is likely to strongly alter interactions between macroalgae (e.g. calcifying and noncalcifying macroalgae; Olabarria et al, 2013;Short et al, 2014Short et al, , 2015, interactions between grazers and macroalgae (Poore et al, 2016;Sampaio et al, 2017), and prey-predator dynamics (Asnaghi et al, 2013;Jellison et al, 2016), inducing drastic consequences on the structure and functioning of marine ecosystems (Widdicombe and Spicer, 2008;Hale et al, 2011).…”
Section: Introductionmentioning
confidence: 99%